Prognostic Significance of Galectin-1 but Not Galectin-3 in Patients With Lung Adenocarcinoma After Radiation Therapy - Huang, Chun-Chieh; Chuang, I-Chieh; Su, Yu-Li; Luo, Hao-Lun; Chang, Ya-Chun; Chen, Jo-Ying; Hsiao, Chang-Chun; Huang, Eng-Yen (Frontiers in Oncology, 2022)
Introduction: To investigate the role of tumor galectin-1 and galectin-3 in patients with lung adenocarcinoma after definitive radiation therapy. Methods: A total of 41 patients with localized lung adenocarcinoma undergoing thoracic radiation therapy without concurrent chemotherapy were enrolled. Their paraffin-embedded lung tissues were sent for immunohistochemical staining for galectin-1 and galectin-3. The clinical treatment outcomes, including overall (OS), locoregional progression-free (LRPFS), and distant metastasis-free (DMFS) survivals were evaluated. Univariable and multivariable Cox regression analyses were applied. Results: Overexpression of tumor galectin-1 and galectin-3 were found in 26.8% and 19.5% of patients, separately. Overexpression of tumor galectin-1 was the most significant prognosticator to predict worse LRPFS both in univariable (p = 0.007) and multivariable analyses (p = 0.022). Besides, patients with overexpression of tumor galectin-1 had trend of worse OS (p = 0.066) than those with low expression in multivariable analysis, and worse DMFS (p = 0.035) in univariable analysis. The overexpression of tumor galectin-3 had no significant effect on survival outcomes. Conclusions: The overexpression of tumor galectin-1, but not galectin-3, is associated with poor LRPFS of patients with lung adenocarcinoma after thoracic radiation therapy. Future research on the mechanism of galectin-1 affecting radiation response in lung adenocarcinoma may be worth exploring.